The court of the Gentiles: or, A discourse touching the original of human literature, both philologie and philosophie, from the Scriptures andJewish church ... - Gale, Theophilus (Puritan collection of English and American literature, 1672)
pt. 1. Of philologie.- pt. 2. Of barbaric and Grecanic philosophie.- pt. 3. The vanity of pagan philosophie demonstrated.- pt. 4. Of reformed philosophie.